2015
DOI: 10.3389/fnagi.2015.00007
|View full text |Cite|
|
Sign up to set email alerts
|

Swept-sine noise-induced damage as a hearing loss model for preclinical assays

Abstract: Mouse models are key tools for studying cochlear alterations in noise-induced hearing loss (NIHL) and for evaluating new therapies. Stimuli used to induce deafness in mice are usually white and octave band noises that include very low frequencies, considering the large mouse auditory range. We designed different sound stimuli, enriched in frequencies up to 20 kHz (“violet” noises) to examine their impact on hearing thresholds and cochlear cytoarchitecture after short exposure. In addition, we developed a cytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 58 publications
2
56
0
Order By: Relevance
“…Increased CAP thresholds were also observed by in adult chinchillas after a 5-day noise exposure, a 40-dB hearing threshold shift was reported by Noreña et al (2003) after a 1-h exposure of adult cats to pure tones at 120 dB. Sanz et al (2015) reported a shift of ABR and DPOAE thresholds in mice exposed for 30 min at the age of 2 months to a violet swept-sine stimulus at 105 or 120 dB SPL.…”
Section: Hearing Thresholds and Auditory Peripherymentioning
confidence: 80%
See 3 more Smart Citations
“…Increased CAP thresholds were also observed by in adult chinchillas after a 5-day noise exposure, a 40-dB hearing threshold shift was reported by Noreña et al (2003) after a 1-h exposure of adult cats to pure tones at 120 dB. Sanz et al (2015) reported a shift of ABR and DPOAE thresholds in mice exposed for 30 min at the age of 2 months to a violet swept-sine stimulus at 105 or 120 dB SPL.…”
Section: Hearing Thresholds and Auditory Peripherymentioning
confidence: 80%
“…However, despite several pioneering works that showed the effects of developmental auditory deprivation (Silverman and Clopton, 1977;Clopton and Silverman, 1978;Coleman and O'Connor, 1979) and suggested that an experience-driven activity during ontogeny is necessary for normal development ConstantinePaton, 1983, 1985;Sanes and Tak acs, 1993), it was not until recently that the importance of proper stimulation and patterned neuronal activity was fully appreciated (e.g., Zhang et al, 2001Zhang et al, , 2002Bao et al, 2003;Chang and Merzenich, 2003;Kandler, 2004;Nakahara et al, 2004;Chang et al, 2005;Kandler and Gillespie, 2005;Zhang et al, 2008;Gr ecov a et al, 2009;Bure s et al, 2010Bure s et al, , 2014Bao et al, 2013). It appears that even a short-time detachment of the developing auditory system from natural and rich auditory experience, resulting from an impaired periphery or anomalous stimulation such as noise or clicks, will often result in altered structural and functional characteristics at various levels of the auditory system.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Laboratory animals are essential for generating accurate models of human hearing loss. One of the articles included in this eBook describes novel models for studying NIHL, based on the use of different sound stimuli, which provide solid ground on which to study potential therapeutic molecules (Sanz et al, 2015). Another important matter that must be addressed is the delivery of potential drugs to the cochlea.…”
mentioning
confidence: 99%